Epistemic Borderwork: Violent Pushbacks, Refugees, and the Politics of Knowledge at the EU Border. (2nd January 2023) - Davies, Thom; Isakjee, Arshad; Obradovic-Wochnik, Jelena
Abstract : Borders are sites of epistemic struggle. Focusing on the illegal tactic of the "pushback, " which is routinely deployed by state authorities to forcefully expel asylum seekers from European Union territory without due process, this article explores the uneven politics of knowledge that helps to support or unsettle this clandestine border violence. Drawing on long-term qualitative research on the Croatia–Bosnia border, including interviews with pushback survivors and activists, as well as a database of border violence reports, we explore the competing truth claims and epistemologies that help to conceal, or counter, the pushback regime. Informed by postcolonial perspectives and contributing to political geographies of violence, we argue that "epistemic violence" (Spivak 1988 ) is a central feature of contemporary borders. We propose that epistemic borderwork is regularly used by state authorities to silence unwanted voices, undermine insurgent perspectives, and stifle the capacity of refugees to draw attention to their own mistreatment. In opposition to this injustice, activists are documenting, mapping, and archiving pushback survivor testimony to construct a counternarrative of refusal, which subverts the harmful knowledge claims of state authorities. In doing so, refugees and activists create epistemic friction, which helps to resist the ontological violence of borders, and "pushes back" against the pushback regime.